Soil exposure is the major fluoride exposure pathways for residents from the high-fluoride karst region in Southwest China. (January 2023) - Li, Fumin; Liao, Shengmei; Zhao, Yifang; Li, Xiangxiang; Wang, Zelan; Liao, Chaoxuan; Sun, Dali; Zhang, Qinghai; Lu, Qinhui
Abstract: In the karst areas of southwest China, soil fluoride levels are higher than in China (478 mg kg −1 ) and world (200 mg kg −1 ). High levels of F in the environment might pose a health risk to humans. The comprehensive exposure risk must be studied in this area. Herein, samples of crops and soil were collected from Bijie City, a typical karst area in southwest China, to investigate the pollution level and evaluate the comprehensive F exposure risk. The single-factor index (PFw ) and the geological accumulation index (Igeo ) were used. The hazard index (HI) was applied to assess exposure risk from multiple exposure routes. The results revealed that there is considerable F contamination in soil and crops in the study area. Average soil total fluorine (Ft) was 1139.13 mg kg −1, and soil water soluble F (Fw) was 3.792 mg kg −1 . In corn, rice, wheat, and potatoes, F contents were 1.167–9.585, 1.222–6.698, 1.587–9.976, and 1.797–9.143 mg kg −1, respectively. The mean values of HI were 4.45 and 2.42 for children and adults, respectively, > 1, showing potential health risk exists. Youngsters are at a greater exposure risk than adults. From the results of contribution ratios of different exposure routes for health risk, the major exposure risk was determined to be from soil exposure. Based on this, we suggest that risk managers mainly strive to control the soil fluoride level and implement the risk education and communication. Graphical abstract: Image 1 Highlights: Serious soil F contamination exists in the Bijie area. Comprehensive health risk assessment of F conducted for local residents. Children are more prone to F exposure than adults. Major F exposure risk is from soil.